(untitled) (Research, Society and Development, 2022)
This study aimed to analyze the vision of elderly people with hearing loss and their spouses about the changes that occurred in their quality of life during the COVID-19 pandemic. This is an exploratory, qualitative, cross-sectional study, in which data were collected by means of an interview conducted via telephone contact with four elderly individuals and their respective spouses who attended a Speech Therapy clinic linked to the Unified Health System (SUS) and located in southern Brazil. The analysis was performed from the content analysis that allowed the division of the answers in three axes: 1) Sociodemographic profile of the sample; 2) Perception of the elderly and spouses about their QL during the pandemic and 3) Changes in QL during the pandemic. According to the data obtained, it was found that the age of the elderly participants and their spouses ranged from 60 to 89 years. The participants with hearing loss corresponded to two elderly males and two elderly females, and their spouses also presented the same proportion in relation to gender, all were married, six participants studied only up to elementary school, and two up to high school. Most of them are retired and live on up to one minimum wage. Most participants perceived a worsening in their QL, especially due to social isolation and restricted interpersonal relationships. It is up to professionals to plan strategies directed to the elderly, allowing them to participate more actively in society, with less anguish and more autonomy, reflecting positively in their QoL.